DEVELOPMENT OF LEADERSHIP SKILL THROUGH INTERNSHIP AS PERCEIVED BY BUSINESS EDUCATION STUDENTS IN UNIVERSITIES IN ANAMBRA STATE (NAU Journal of Technology and Vocational Education, 2024)
This study focused on the development of leadership skills through internship as perceived bybusiness education students in universities in Anambra State. One research question guided thestudy while one null hypothesis was tested at 0.05 level of significance. The study adopteddescriptive survey research design. The population of the study consisted of 619 businesseducation students in the three universities offering the programme. The entire population wasused for the study. A structured questionnaire was the instrument used for data collection. Thereliability of the instrument was established using Cronbach’s alpha and it yielded an overallcoefficient of 0.81. Mean and standard deviation were used to analyse data to answer theresearch question and determine the cohesiveness or otherwise of respondents’ mean rating. ttest was used to test the null hypothesis. The findings of the study revealed that the studentsperceive internship as a model for the development of leadership skills. However, the resultshows that male and female business education students differ significantly in their mean ratingsregarding how they perceive the development of leadership skills in internship. Based on thefinding, it was concluded that business education students perceive internship as a model thatwill increase leadership skill development. Consequently, it was recommended among othersthat there is need for a structured leadership skill acquisition programme for business educationstudents
Keywords: Business education, leadership skills, internship.